Who Owns Big Pharma and the Billionaires Invested in the Gender Industry? - Bilek, Jennifer (The 11th Hour Blog, 2021)
There is no “transgender” community that pushes an ideology of body dissociation around the world—at lightning speed—into language, law, institutions, and the media simultaneously. We are governed by oligarchs at the highest echelons of finance, and they have a vested interest in the gender industry. “Gender identity” ideology is not politically separate from business. Business is no longer separate from politics. We in Western cultures are governed by billionaires in finance who drive policy th